PENYULUHAN PEMBUATAN AMELIORAN SEBAGAI BAHAN PEMBENAH TANAH DI DESA PEMENANG BARAT - Astiko, Wahyu; Fauzi, M. Taufik; Sudantha, I Made; Sudirman, Sudirman; Ernawati, Ni Made Laksmi; Muthahanas, Irwan (Universitas Mataram, 2024)
Pemenang Barat Village is one of the villages in the North Lombok Region whose land is dominated by sandy soil, has a dry climate and low rainfall. This sandy soil is porous, poor in nutrients and organic matter. This condition causes plant growth and yield to be low and can even cause harvest failure. Through this community service activity,